Exploring the perception of pictorial health warnings on tobacco package among the patients attending Dental Institute in Ahmedabad City - Mahek R Zen; Sujal M Parkar (Queeva Publishing, 2026)
Background: Tobacco use remains a significant global public health challenge. WHO Framework Convention on Tobacco Control mandates that nations take steps to ensure that tobacco product packaging carries health warnings and messages. This study aims to explore the perception of pictorial health warnings (PHWs) on tobacco packages among the patients attending dental institute in Ahmedabad city. Methods: A cross-sectional questionnaire study was conducted among 210 patients attending dental institute in Ahmedabad city. The data were collected through face-to-face interview by using a self-designed, pre-tested questionnaire. The questionnaire consists of questions pertaining to demographic details, tobacco related habits and perception on PHWs. Data was analyzed using descriptive statistics. Multivariate logistic regression analysis was performed to identify independent predictors for perception of PHWs. Result: More than half of the subjects (n=129, 61.43%) were having current habit of tobacco consumption in any form. Total 197 (93.80%) were aware about health warning messages on tobacco packages. Among 197 respondents, 67 (34.00%) respondents noticed only PHWs. Total 136(69.04%) subjects had perception of imagine health harms after seeing PHWs and 132(67.00%) subjects were worried for their health. More than half (n=64, 55.17%) wants to quit habit after seeing PHWs. Among individuals with a habit of tobacco consumption, the likelihood of imagining health harms (OR = 3.61, 95% CI: 1.73–7.53) and feeling worried about their health after viewing PHWs (OR = 3.61, 95% CI: 1.73–7.53) was significantly higher (p < 0.001). Conclusion: There was a favorable perception and positive impact on tobacco users to quit the habit.